2018
DOI: 10.2147/jpr.s176468
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin to improve postoperative recovery in bariatric surgery: a parallel, randomized, doubleblinded, placebo-controlled study

Abstract: PurposeObesity has been considered as a major public health problem in developed countries for which bariatric surgery has become an important treatment strategy. Postoperative pain, however, is a frequent problem in postoperative management. Pregabalin blocks the development of hyperalgesia and central pain sensitization. The objective of this randomized, placebo-controlled, double-blinded trial was to evaluate the effect of a single dose of preoperative pregabalin vs placebo on the quality of postoperative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…A Korean study with healthy patients showed no increase in adverse effects when combining tramadol with pregabalin Lee [37]. Similar results with the use of pregabalin for postoperative pain reduction were found by Martins [36], Zhang [31], Mathiesen [15] respectively after bariatric cholecystectomy and hip arthroplasty procedure. In a postoperative TKA study following pregabalin use for another 3 months no patient had a common adverse effect of pregabalin even though the study addressed an extensive list of endocrine, [35].…”
Section: Unwanted Effectssupporting
confidence: 64%
See 1 more Smart Citation
“…A Korean study with healthy patients showed no increase in adverse effects when combining tramadol with pregabalin Lee [37]. Similar results with the use of pregabalin for postoperative pain reduction were found by Martins [36], Zhang [31], Mathiesen [15] respectively after bariatric cholecystectomy and hip arthroplasty procedure. In a postoperative TKA study following pregabalin use for another 3 months no patient had a common adverse effect of pregabalin even though the study addressed an extensive list of endocrine, [35].…”
Section: Unwanted Effectssupporting
confidence: 64%
“…Again, it was shown that there was no improvement in the quality of postoperative patient recovery and not even pain reduction Martins Et Al. [36]. As the effectiveness of postoperative pain reduction has been demonstrated with dosages of 150mg and 300mg Singla et al [37] these interpretations become questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids continue to play an important role in controlling postoperative pain; however, they are not exempt from side effects, and a multimodal approach has been suggested to improve postoperative analgesia and, at the same time, mitigate these side effects 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin is more widely studied as an adjuvant to improve perioperative pain management in bariatric anesthesia with mixed results. [ 22 ] Even if started in the postoperative period, gabapentin and pregabalin may increase sedation and potentiate opioid-induced respiratory depression, adversely impact sleep architecture, and impair balance and vision. Their use in the perioperative period should require a very careful assessment of the risk–benefit in patients after bariatric surgery, especially those with OSA.…”
Section: Gabapentinoidsmentioning
confidence: 99%
“…Their use in the perioperative period should require a very careful assessment of the risk–benefit in patients after bariatric surgery, especially those with OSA. [ 21 22 ] Hence, the routine use of the gabapentinoids is not useful or justified in bariatric anesthesia unless the patient is already on them or develops acute hyperalgesia postoperatively.…”
Section: Gabapentinoidsmentioning
confidence: 99%